The Europeanization of Romanian Foreign Policy: Mitigating European and National ‘Misfits’ in the International Criminal Court and Kosovo Cases - Mircea Micu (Romanian Journal of European Affairs, 2011)
This article aims to tackle some of the challenges posed to the Europeanization research agenda and to examine the usefulness of the Europeanization approach to the study of national foreign policy (selecting Romania as a test case). It proposes a research design that lays emphasis on pinpointing and mitigating the ‘misfit’ between EU and national levels, and on the role of the ‘political vulnerability’ stemming from the EU conditionality imposed on candidate countries and from different perceptions of threat. The two case studies chosen refer to EU-Romanian disagreements over the International Criminal Court’s jurisdiction and Kosovo’s unilateral declaration of independence.